Virtual Reality Stroop Task for neurocognitive assessment - Parsons, Thomas D; Courtney, Christopher G; Arizmendi, Brian; Dawson, Michael (Studies in health technology and informatics, 2011)
Given the prevalence of traumatic brain injury (TBI), and the fact that many mild TBIs have no external marker of injury, there is a pressing need for innovative assessment technology. The demand for assessment that goes beyond traditional paper-and-pencil testing has resulted in the use of automated cognitive testing for increased precision and efficiency; and the use of virtual environment technology for enhanced ecological validity and increased function-based assessment. To address these issues, a Virtual Reality Stroop Task (VRST) that involves the subject being immersed in a virtual Humvee as Stroop stimuli appear on the windshield was developed. This study is an initial validation of the VRST as an assessment of neurocognitive functioning. When compared to the paper-and-pencil, as well as Automated Neuropsychological Assessment Metrics versions of the Stroop, the VRST appears to have enhanced capacity for providing an indication of a participant's reaction time and ability to inhibit a prepotent response while immersed in a military relevant simulation that presents psychophysiologically arousing high and low threat stimuli.